Vice Chancellor's Leadership Policy in Improving Lecturer Performance: A Case Study in East Kalimantan - Zaenab Hanim; Lukman Priyandono; Rahmat Soe’oed (EduLine: Journal of Education and Learning Innovation, 2022)
This study aims to describe the formulation, implementation, constraints, and solutions of the vice chancellor's leadership policies in improving the performance of lecturers at private universities in East Kalimantan. This research uses a qualitative approach with the type of case study research. The data collection involved three informants, namely the Vice-Chancellor I for academics and planning, the Dean of the Faculty of Teacher Training and Education, and lecturers. Data collection techniques through observation, interviews, and documentation. The data analysis used is the Miles and Huberman model, which includes data collection, data reduction, data presentation, and drawing conclusions. The results showed that: (1) the vice chancellor's leadership policies in improving lecturer performance were defining problems, analyzing problems, receiving suggestions and input from lecturers, deciding the best solution, and implementing policies, and (2) the obstacles faced by the vice chancellor when determining policies were discipline. lecturers, the competence of lecturers in the fields of research, scientific publications, and community service as well as the lack of Personnel for Research and Community Service Institutions, (3) the vice chancellor's efforts to resolve policy problems are to give advice to lecturers who are not disciplined, to give rewards to lecturers who obedience, increase the number of personnel for Research and Community Service Institutions and establish Partnership and Entrepreneurship Studies.